2017
DOI: 10.1038/s41467-017-02367-6
|View full text |Cite
|
Sign up to set email alerts
|

VGLUT1 functions as a glutamate/proton exchanger with chloride channel activity in hippocampal glutamatergic synapses

Abstract: Glutamate is the major excitatory transmitter in the vertebrate nervous system. To maintain synaptic efficacy, recycling synaptic vesicles (SV) are refilled with glutamate by vesicular glutamate transporters (VGLUTs). The dynamics and mechanism of glutamate uptake in intact neurons are still largely unknown. Here, we show by live-cell imaging with pH- and chloride-sensitive fluorescent probes in cultured hippocampal neurons of wild-type and VGLUT1-deficient mice that in SVs VGLUT functions as a glutamate/proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…ClC‐3 was reported to support the acidification of endosomes (Yoshikawa et al , ; Hara‐Chikuma et al , 2005b; Weylandt et al , ) and SVs (Stobrawa et al , ; Riazanski et al , ) by providing an electric shunt for proton pumping. However, more recent work (Schenck et al , ) suggested that impaired SV acidification in Clcn3 −/− mice may rather be due to the observed reduction in the levels of VGLUT1 (Stobrawa et al , ), which, in addition to its role as glutamate transporter, may also conduct Cl − (Schenck et al , ; Preobraschenski et al , ; Eriksen et al , ; Martineau et al , ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ClC‐3 was reported to support the acidification of endosomes (Yoshikawa et al , ; Hara‐Chikuma et al , 2005b; Weylandt et al , ) and SVs (Stobrawa et al , ; Riazanski et al , ) by providing an electric shunt for proton pumping. However, more recent work (Schenck et al , ) suggested that impaired SV acidification in Clcn3 −/− mice may rather be due to the observed reduction in the levels of VGLUT1 (Stobrawa et al , ), which, in addition to its role as glutamate transporter, may also conduct Cl − (Schenck et al , ; Preobraschenski et al , ; Eriksen et al , ; Martineau et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Our present work supports the suggestion of Takamori and colleagues (Schenck et al , ) that the reduced acidification of SVs from Clcn3 −/− mice (Stobrawa et al , ) can be attributed to a reduction of the vesicular glutamate transporter VGLUT1 which we had observed earlier (Stobrawa et al , ). VGLUT1 appears to operate in several modes which includes a Cl − conductance (Schenck et al , ; Preobraschenski et al , ; Martineau et al , ). The fact that > 65% of purified SVs are glutamatergic (Takamori et al , ) is compatible with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we unexpectedly discovered a significantly larger SV super-pool in the axons of vglut1 -/neurons (Siksou et al, 2013). Also, Vglut1 -/-SVs appear pleomorphic under hyperosmotic chemical fixation (Herman et al, 2014;Siksou et al, 2013), however this latter phenotype is most likely a direct consequence of a major change in the ionic composition of the SV lumen (Eriksen et al, 2016;Martineau et al, 2017;Preobraschenski et al, 2014;Schenck et al, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…Synaptic efficacy depends on the presynaptic and postsynaptic compartments. In particular, synapsin1, vesicular glutamate transporters (VGluT1), PSD95, and Homer1a are classical markers of presynaptic and postsynaptic proteins, which play an important role in synaptic activity [54][55][56][57][58][59]. Previous research has reported that the repeated sevoflurane exposure downregulates synaptic proteins such as postsynaptic protein PSD95 in the hippocampus of developing mice [60,61].…”
Section: Resveratrol Restored Synaptic Protein Expression Ex Vivomentioning
confidence: 99%